Representation of Indonesian women workers: a critical discourse analysis on the newspapers of nationalist-secular and Islamic ideological perspectives - Aris Badara; Jamiludin Jamiludin (IAIN Salatiga, 2020)
The purpose of this study is to reveal the representation of women workers in newspaper news discourse that follows the nationalist-secular ideology and the Islamic ideology perspectives. The method of this research is a qualitative content analysis that views the text as a symbolic message and it requires interpretation according to the context. Complementing the research method, a critical discourse analysis approach is also used. The subjects of this research are female workers found in newspaper news discourse that carries the values of Islamic ideology and newspapers that carry nationalist-secular ideology. Data were analyzed through critical discourse analysis techniques in the following steps: (a) description; (b) interpretation; and (c) explanation. This research still considers checking the reliability and the validity. Data analysis is also complemented by confirmation of linguists and peers (triangulation of sources). The main findings of this study show that the practice of discourse in the RM newspaper which follows the nationalist-secular ideology perspective represents marginal women. By the RM newspaper, the representation is used as a plea for the actions and trait of male actors or employers. The motive revealed from this phenomenon is to follow the demand of the market. On the other hand, the newspaper R, which tends to follow Islamic ideology perspective, represents the motive of advocacy for women workers. This is the implication of the values of Islamic ideology carried out by the R newspaper as mentioned in its vision and mission. The findings are also the antithesis of the view that Islam isolates women in the social sphere of society.Tujuan penelitian ini ialah mengungkap representasi pekerja perempuan pada wacana berita surat kabar yang berpresfektif ideologi nasionalis-sekuler dan surat kabar yang berpersfektif ideologi Islam. Metode penelitian ini ialah analisis isi kualitatif yang memandang teks sebagai suatu pesan simbolik yang perlu diinterpretasi sesuai dengan konteks. Melengkapi metode penelitian tersebut, digunakan pendekatan analisis wacana kritis. Latar penelitian ini ialah pekerja perempuan yang terdapat pada wacana berita surat kabar yang megusung nilainilai ideologi Islam dan surat kabar yang mengusung ideologi nasionalis-sekuler. Data dianalisis melalui teknik analisis wacana kritis dengan langkah: deskripsi, interpretasi, dan eksplanasi. Penelitian ini tetap mempertimbangkan checking the reliability dan checking the validity. Analisis data dilengkapi comfirmability melalui pakar bahasa dan sejawat (trianggulasi sumber). Temuan utama penelitian ini menunjukkan bahwa praktik wacana pada berita Surat kabar Rakyat Merdeka yang berideologi nasionalis-sekuler merepresentasi perempuan secara marjinal. Representasi tersebut dijadikan pleidoi atas perlakuan majikan. Motif yang diungkap ialah mengikuti permintaan ‘pasar’. Adapun Surat Kabar Republika, cenderung ke ideologi Islam, merepresentasi pekerja perempuan secara apa adanya dengan motif untuk melakukan advokasi. Hal tersebut merupakan implikasi dari nilai-nilai ideologi Islam yang diemban oleh surat Kabar tersebut. Temuan tersebut juga menjadi antitesis dari pandangan yang menyatakan Islam melakukan pengucilan terhadap perempuan dalam sosial-kemasyarakatan.